Activating cGAS-STING pathway with ROS-responsive nanoparticles delivering a hybrid prodrug for enhanced chemo-immunotherapy. (November 2022) - Cao, Lei; Tian, Huixiang; Fang, Man; Xu, Zhe; Tang, Dongsheng; Chen, Juan; Yin, Jiye; Xiao, Haihua; Shang, Kun; Han, Hongbin; Li, Xiangping
Abstract: cGAS-STING pathway, as an essential intracellular immune response pathway, has attracted much attention in tumor immunotherapy. However, low metabolic stability of conventional STING agonists limits their clinical application. Recent study shows that chemotherapeutic drugs cisplatin and camptothecin (CPT) can activate cGAS-STING pathway and induce immune response by DNA damage. Nevertheless, the ability of chemotherapeutic drugs to activate STING is so weak that new strategies are required to improve drug delivery efficiency for enhanced DNA damage, and then efficiently activate cGAS-STING pathway. Herein, we have developed a hybrid platinum prodrug (CPT-Pt (IV)) which can be triggered to release cisplatin and CPT in tumor cells. CPT-Pt (IV) with high hydrophobicity is further self-assembled with a ROS sensitive polymer (P1) and mPEG2k -DSPE into ROS responsive nanoparticles (NPs). NPs could accumulate in the tumor site to release cisplatin and CPT, resulting in DNA double damage and finally activating cGAS-STING pathway, inducing DC cells maturation and increasing tumor infiltration of CD8 + T cells on colorectal cancer mouse model. This study showed that common DNA targeted drugs can activate the cGAS-STING pathway in situ via nano delivery system, and enhance the effect of chemotherapy and immunotherapy, which provide a new strategy for clinical antitumor therapy.